2023
DOI: 10.3390/horticulturae9101077
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients Use Efficiency in Coupled and Decoupled Aquaponic Systems

Maria Aslanidou,
Angeliki Elvanidi,
Anastasia Mourantian
et al.

Abstract: Aquaponics is currently undergoing a transformation into an intensive food production system. The initially applied systems focused on small-scale, fish-centric coupled (CAP, the aquaculture, and the hydroponic units are arranged in a single loop, and the water flows continuously from the fish tanks to the plant unit and back) aquaponics. More recently, the primary area of research interest has shifted toward larger-scale, plant-centric decoupled (aquaculture and hydroponics units are arranged in a multi-loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The limitations of CAP became evident from the initial harvest on D26, and by the final harvest on D54, there was an 80% reduction in aerial part fresh weight and a 28.7% decrease in leaf number. Previous studies have also reported lower yields in coupled systems compared to hydroponics [8,9,11,23]. Lettuce is a frequently studied species in the aquaponics literature [24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The limitations of CAP became evident from the initial harvest on D26, and by the final harvest on D54, there was an 80% reduction in aerial part fresh weight and a 28.7% decrease in leaf number. Previous studies have also reported lower yields in coupled systems compared to hydroponics [8,9,11,23]. Lettuce is a frequently studied species in the aquaponics literature [24].…”
Section: Discussionmentioning
confidence: 99%
“…The largest area is covered by the hydroponics unit (360 m 2 ) where the crops are cultivated, while the RAS is installed in a closed chamber (80 m 2 ) under controlled environmental conditions. A full description of both the hydroponics and the RAS sub-systems, as well as the environmental control within the RAS chamber and the whole greenhouse, can be found in our previous articles [8,9]. Briefly, the RAS sub-system comprises three fish tanks, each with a volume of 1.3 m 3 , connected with the mechanical filter (0.5 m 3 , Combi Bio 15, ProfiDrum, Retford, UK) and the bio-filter.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations